Dialysis Duration and Glucose Exposure Amount Do Not Increase Mortality Risk in Peritoneal Dialysis Patients: A Population-Based Cohort Study From 2004 to 2012 - Wu, Pei-Yu; Lin, Ming-Yen; Hwang, Shang-Jyh; Chiu, Yi-Wen (Frontiers in Medicine, 2022)
Background: Although the bio-incompatibility of glucose-based peritoneal dialysis(PD) solution is well documented, it is used worldwide. How PD duration and the amount of dialysate glucose exposure affect survival in end-stage renal disease patients remains inconclusive due to improper study designs in extant literature. Methods: All incident PD patients from 2004 through 2007 and older than 18-years-old in Taiwan were included. Patients were censored when they received a transplant or at the end of 2012. Glucose exposure through PD solution was calculated by mean glucose contained per liter when receiving PD. For those who already shifted to hemodialysis(HD) and survived longer than 2, 3, and 4 years (the index dates), a Cox regression model was used to make the survival comparison by PD duration and mean glucose concentration in these three cohorts, respectively. The model was adjusted by demographics, case-mix, time cohort (2004-2005 vs.2006-2007), peritonitis episode (none vs. ≧once), and mean PD solution glucose exposure (tertile). Results: A total of 3,226 patients were included with a mean age of 53.4±15.2 years, male 44.6%, and 34.2% having diabetes mellitus. The 1, 2, 3, and 4-year survival rates were 94%, 87%, 80%, and 74%,while technical survival rates were 86%, 70%, 56%, and 45%, respectively. The overall transplant events were 309(9.6%) only. There were 389, 495, and 553 incident PD patients shifting to HD included in 2-, 3-, and 4-year cohort, respectively. The population with moderate glucose concentration exposure had the highest mortality, and the high glucose concentration exposure had non-significant lower mortality in each cohort. In various fixed time-window cohorts, the duration of PD treatment did not increase mortality risk after adjustments. In addition, glucose exposure did not affect mortality rate. Conclusion: For incident PD patients with PD duration no longer than 4years, neither PD duration nor glucose exposure amount increases long-term mortality risk.